LAMANYA PEMBENAMAN PAKU AIR (Azolla pinnata L.) SEBAGAI PUPUK HIJAU UNTUK MENINGKATKAN PRODUKSI TANAMAN SAWI (Brassica rafa L.) - Inka Dahlianah (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2013)
Research has been carried out in the garden 8 Ilir Palembang from August to September 2012, to determine how long the incubation water fern (Azolla pinnata L.) as green manure for cultivation of mustard (Brassica rafa L.). This study used a completely randomized design (CRD) with five treatments were replication 4 times. The long incubation treatment factors are as follows: I1 (7 days), I2 (14 days), I3 (21 days), I4 (28), and I5 (35 days). The results showed that treatment results I5 (42 days) showed the highest yield is 1,00 kg per m2 compared with other treatments. Key words: green manure, Azolla pinnata